Ionomic Responses of Local Plant Species to Natural Edaphic Mineral Variations - Zhang, Chengming; Hiradate, Syuntaro; Kusumoto, Yoshinobu; Morita, Sayaka; Koyanagi, Tomoyo F.; Chu, Qingnan; Watanabe, Toshihiro (Frontiers in Plant Science, 2021)
Leaf ionome indicates plant phylogenetic evolution and responses to environmental stress, which is a critical influential factor to the structure of species populations in local edaphic sites. However, little is known about leaf ionomic responses of local plant species to natural edaphic mineral variations. In the present study, all plant species and soil samples from a total of 80 soil sites in Shiozuka Highland were collected for multi-elemental analysis. Ioniomic data of species were used for statistical analysis, representing 24 species and 10 families. Specific preferences to ionomic accumulation in plants were obviously affected by the phylogeny, whereas edaphic impacts were also strong but limited within the phylogenetic preset. Correlations among elements resulted from not only elemental synergy and competition but also the adaptive evolution to withstand environmental stresses. Furthermore, ionomic differences of plant families were mainly derived from nonessential elements. The majority of variations in leaf ionome is undoubtedly regulated by evolutionary factors, but externalities especially environmental stresses also have an important regulating function for landscape formation, determining that the contributions of each factor to ionomic variations of plant species for adaptation to environmental stress provides a new insight for further research on ionomic responses of ecological speciation to environmental perturbations and their corresponding adaptive evolutions.